Area Studies and Social Science Strategies for Understanding Middle East Politics - Peters, Joel (Hagar: Studies in Society and Culture, 2001)
The article reviews the book "Area Studies and Social Science Strategies for Understanding Middle East Politics," edited by Mark Tessler, Jodi Nachtwey, and Anne Banda.